Antigen presentation safeguards the integrity of the hematopoietic stem cell pool - Hernández-Malmierca, Pablo; Vonficht, Dominik; Schnell, Alexandra; Uckelmann, Hannah J.; Bollhagen, Alina; Mahmoud, Mohamed A. A.; Landua, Sophie-Luise; van der Salm, Elise; Trautmann, Christine L.; Raffel, Simon; Grünschläger, Florian; Lutz, Raphael; et al. (Cell stem cell, 2022)
Hematopoietic stem and progenitor cells (HSPCs) are responsible for the production of blood and immune cells. Throughout life, HSPCs acquire oncogenic aberrations that can cause hematological cancers. Although molecular programs maintaining stem cell integrity have been identified, safety mechanisms eliminating malignant HSPCs from the stem cell pool remain poorly characterized. Here, we show that HSPCs constitutively present antigens via major histocompatibility complex class II. The presentation of immunogenic antigens, as occurring during malignant transformation, triggers bidirectional interactions between HSPCs and antigen-specific CD4+ T cells, causing stem cell proliferation, differentiation, and specific exhaustion of aberrant HSPCs. This immunosurveillance mechanism effectively eliminates transformed HSPCs from the hematopoietic system, thereby preventing leukemia onset. Together, our data reveal a bidirectional interaction between HSPCs and CD4+ T cells, demonstrating that HSPCs are not only passive receivers of immunological signals but also actively engage in adaptive immune responses to safeguard the integrity of the stem cell pool.
Gesehen am 20.07.2022